The Masquelet Technique: Can Disposable Polypropylene Syringes be an Alternative to Standard PMMA Spacers? A Rat Bone Defect Model - Mathieu, Laurent; Murison, James Charles; de Rousiers, Arnaud; de l'Escalopier, Nicolas; Lutomski, Didier; Collombet, Jean-Marc; Durand, Marjorie (Clinical orthopaedics and related research, 2021)
Usually, the two-stage Masquelet induced-membrane technique for extremity reconstruction begins with a polymethylmethacrylate (PMMA) cement spacer-driven membrane, followed by an autologous cancellous bone graft implanted into the membrane cavity to promote healing of large bone defects. In exceptional cases, spacers made of polypropylene disposable syringes were successfully used instead of the usual PMMA spacers because of a PMMA cement shortage caused by a lack of resources. However, this approach lacks clinical evidence and requires experimental validation before being recommended as an alternative to the conventional technique. To (1) develop and (2) validate a critical-sized femoral defect model in rats for two stages of the Masquelet technique and to (3) compare the biological and bone healing properties of polypropylene-induced membranes and PMMA-induced membranes in this model. Fifty male Sprague Dawley rats aged 8 weeks old received a 6-mm femur defect, which was stabilized with an external fixator that was converted into an internal device. In the development phase, the defect was filled with PMMA in 16 rats to determine the most favorable timing for bone grafting. Two rats were excluded since they died of anesthetic complications. The other 14 were successively euthanized after 2 weeks (n = 3), 4 weeks (n = 4), 6 weeks (n = 4), and 8 weeks (n = 3) for induced membrane analyses. In the validation phase, 12 rats underwent both stages of the procedure using a PMMA spacer and were randomly assigned to two groups, whether the induced membrane was preserved or removed before grafting. To address our final objective, we implanted either polypropylene or PMMA spacers into the defect (Masquelet technique Stage 1; n = 11 rats per group) for the period established by the development phase. In each group, 6 of 11 rats were euthanized to compare the biological properties of polypropylene-induced membranes and PMMA-induced membranes using histological qualitative analysis, semiquantitative assessment of the bone morphogenic protein-2 content by immunostaining, and qualitative assessment of the mesenchymal stromal cell (MSC; CD31-, CD45-, CD90+, and CD73+ phenotypes) content by flow cytometry. Quantitative measurements from serum bone turnover markers were also performed. The five remaining rats of each group were used for Masquelet technique Stage 2, in which rat bone allografts were implanted in the induced membrane cavity after the polypropylene or PMMA spacers were removed. These rats recovered for 10 weeks before being euthanized for microCT quantitative measurements and bone histology qualitative assessment to evaluate and compare the extent of bone regeneration between groups. Induced membrane analyses together with serum bone turnover measurements indicated that a 4-week interval time between stages was the most favorable. Removal of the induced membrane before grafting led to almost constant early implant failures with poor bone formation. Four-week-old rats with polypropylene-triggered induced membranes displayed similar histologic organization as rats with PMMA-driven induced membranes, without any difference in the cell density of the extracellular matrix (4933 ± 916 cells per mm2 for polypropylene versus 4923 ± 1284 cells per mm2 for PMMA; p = 0.98). Induced membrane-derived MSCs were found in both groups with no difference (4 of 5 with polypropylene versus 3 of 3 with PMMA; p > 0.99). Induced membrane bone morphogenic protein-2 immunolabeling and serum bone turnover marker levels were comparable between the polypropylene and PMMA groups. MicroCT analysis found that bone regeneration in the polypropylene group seemed comparable with that in the PMMA group (29 ± 26 mm3 for polypropylene versus 24 ± 18 mm3 for PMMA; p > 0.99). Finally, qualitative histological assessment revealed a satisfactory endochondral ossification maturation in both groups. Using a critical-sized femoral defect model in rats, we demonstrated that polypropylene spacers could induce membrane encapsulation with histologic characteristics and bone regenerative capacities that seem like those of PMMA spacers. In a same bone site, polymers with close physical properties seem to lead to similar foreign body reactions and induce encapsulating membranes with comparable bone healing properties. Polypropylene spacers made from disposable syringes could be a valuable alternative to PMMA. These results support the possibility of a cementless Masquelet technique in cases of PMMA shortage caused by a lack of resources.